Pemanfaatan Firewall dan Metode Queue Tree Sebagai Traffic Filtering Akses Pengguna Jaringan Internet - ilham Faisal; T.M. Diansyah (LPPM STIKOM Tunas Bangsa, 2024)
The use of internet networks that are not monitored and controlled with policies will certainly cause violations. Violations can include prohibited access, theft, and excessive bandwidth usage. Such as accessing sites that require bandwidth usage when opening online videos, games, downloading videos and so on. If in an office or workspace there are several computer users who do this, then other computers will experience problems with access to work. This research analyzes the use of firewalls in performing traffic filtering on the internet network with a focus on Layer 7 protocol filters. This research is expected to provide practical guidance for organizations or companies in making the right decisions regarding the use of Layer 7 protocol filters in their organization's network security strategy. In addition, the test results provide valuable insights for network administrators to optimize firewall configuration and improve internet access control as well as protection against network security threats. The test results show that the average traffic limit successfully implemented using Layer 7 protocol filters is approximately 14.5%. This result reflects the firewall's ability to distinguish and block certain applications or services running over the same application protocol.